The Urgency of Indonesian Public Policy in Facing a War Situation in the Peace of Global Economic Competition - Rianto, Rianto; Prakoso, Lukman Yudho; Alman, Fariel Zulfikar; Soemantri, Asep Iwa; Patmi, Sri; Bermana, Seftiandra; Habibie, Sri Yaumil; Al-Mujaddid, Toriq Furqon (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article discusses the urgency of Indonesian public policy in facing the situation of